THE SYSTEM OF SANCTIONS FOR INTERNATIONAL CRIMINAL OFFENSES - Miodrag N. Simović; Vladimir M. Simović (Годишњак Правног факултета у Бањалуци)
International criminal law as a supranational, universal set of legal regulations determines the concept and elements of international criminal offenses that violate and infringe international law, thereby violating or jeopardizing universal values, goods and interests protected by international law, and criminal sanctions as measures of social reaction against perpetrators of these offenses. For the application of criminal sanctions against the perpetrators of international criminal offenses, the competent judicial authorities (at the level of the international community) determine the basis of their criminal responsibility in the procedure they conduct. In the system of sanctions, which should fulfill both preventive and repressive role, there are penalties whose application is linked to prescribed requirements. These international sanctions have primacy in relation to criminal sanctions prescribed for similar/identical international criminal offenses by individual national criminal legislations, including the legislation of Bosnia and Herzegovina. The paper discusses the concept, elements, content, purpose, characteristics and types of criminal sanctions for international criminal offenses.